Seromonitoring of Peste des Petits Ruminants in goats and molecular characterization of PPR virus from field cases - Ahamed, Shamim; Nazir, KHM Nazmul Hussain; Yousuf, Md Abu; Islam, Md Monowarul; Arafat, Md Yeasin; Islam, Md Ariful; Mahmud, Md Muket; Islam, Md Rafiqul (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: The study was undertaken with the objectives to perform seromonitoring of Peste des Petits Ruminants (PPR) antibodies in goats vaccinated with PPR vaccine and molecular characterization of PPR virus (PPRV) from field cases in Bangladesh. Materials and Methods: Seromonitoring work was conducted in Char Kalibari, Mymensingh Sadar, Mymensingh. For this, a total of 50 goats were randomly selected and were divided into two groups; vaccinated (Group A; n = 25) and non-vaccinated (Group B; n = 25). The goats of both groups were again sub-divided into four age groups; (i) 0–6 months (n = 5), (ii) 6–12 months (n = 5), (iii) 12–24 months (n = 10), and (iv) >24 months (n = 5). Blood samples were collected on Day-0 and after 21 days of post-vaccination (DPV), and the sera were prepared. The sera were examined for the presence of antibodies against PPRV by competitive enzyme-linked immunosorbent assay. For molecular characterization, nasal swabs (n = 10) were collected from PPR infected goats in Jessore during PPR outbreak (February 2016). The causative agent, PPRV isolated from field cases were confirmed by N gene based on reverse transcription polymerase chain reaction (RT-PCR), followed by sequencing, phylogenetic analysis, and multiple sequence alignment analyses. Results: In the case of seromonitoring, the results revealed that before vaccination (at Day-0), overall, 44% (n = 22/50) goats were seropositive for PPRV. In Group A, 48% (n = 12/25) goats were seropositive, but after 21 DPV, 96% (n = 24/25) goats become seropositive. On the other hand, in Group B, 40% (n = 10/25) and 16% (n = 04/25) seropositive goats found at Day-0 and after 21 DPV, respectively, indicating that the antibody titer was increasing after vaccination and decreasing in convalescent goats. Out of 10 nasal swab samples, 40% (n = 4/10) was confirmed by RT-PCR targeting nucleocapsid (N gene). Phylogenetically, our isolate (KY039156/PPRV/BDG/Jes/2016) was similar to the other strains of PPRV under lineage IV. However, there was a unique amino acid substitution, where glycine (G) was recorded in place of arginine (R). The strain is closely related with other Chinese or Indian strains. The nucleotide sequence homology by NCBI BLAST search of the isolated strain ranged from 95% to 99% with other strains circulating in Bangladesh. Conclusion: The PPRV is prevailing in the Mymensingh and Jessore regions of Bangladesh. Effective control of PPR in goats may depend on vaccination with PPR vaccine. Molecular characterization of PPRV in Jessore reveals that the virus is differing from the strain prevalent in other regions of Bangladesh and the world. J. Adv. Vet. Anim. Res., 6(3): 416-424, September 2019